Multimodal analysis of the thematic organization of audio description scripts for two-dimensional artworks: a case study via systemic functional perspective - Arraes, Daniel de Albuquerque e (2021)
Audio description (AD) is an Audiovisual Translation modality that tries to address the sensory needs of people with visual impairment, allowing them to obtain through words the information otherwise perceived only through visual input. Regarding the research on AD carried out in Brazil, XXXX (2014) developed an analysis model – called XXXX’s Systemic Functional Semiotic Model (Portuguese acronym, MSSFA) – to help in-training professionals of AD. This model results from the interface between O’toole’s (1990, 1994, 1995, 2011) Systemic Functional semiotic model and the studies of De Coster and Mühleis (2007), Holland (2009) and Magalhães & Araújo (2012). The experience of applying it in the training of AD professionals has shown that it cannot handle the linguistic matters of AD, since its main concern is to offer parameters of visual literacy. This paper identifies a paucity of research that looks at the construal of texture in AD for two-dimensional artwork; therefore, it aims at contributing with the textual production stemming from visual reading and interpretation. This is a case study that analyzes one artwork (‘Frida y Diego Rivera’, painted by Frida Kahlo in 1931) and two AD scripts describing it (one script was produced by an AD professional in training and the other was improved by an experienced AD professional). The artwork is analyzed using the MSSFA model, while the AD scripts are analyzed using the resource of Periodicity (MARTIN, 1992, MARTIN; ROSE, 2007) of Systemic Funcional Linguistics (HALLIDAY; MATTHIESSEN, 2014).